Finding clues in the p53 maze: an interview with Karen Vousden - Karen Vousden (The Company of Biologists, 2018)
Karen Vousden is an internationally renowned cancer scientist whose contributions to solving the p53 puzzle are changing the way we think about this important tumour suppressor. She has been honoured with many prizes and elected memberships throughout her career, and was appointed Commander of the Order of the British Empire (CBE) in 2010 and Foreign Associate of the US National Academy of Sciences in May 2018. Karen is an approachable and diligent scientist, a respected mentor and an inspirational role model. She is currently a group leader at the Francis Crick Institute in London and Chief Scientist at Cancer Research UK (CRUK). In this interview, Karen talks about the mentors that inspired her, the discoveries that brought about her interest in cancer metabolism, and her interests outside the lab. Karen Vousden's research focuses on the many functions of p53 in cancer and beyond. Her scientific journey in the field of genetics started with undergraduate and graduate work on transfer RNA (tRNA) suppression with Lorna Casselton at the University of London, UK. She studied Ras and viral oncogenes during her postdoctoral training with Christopher Marshall and Douglas Lowy. The interactions between viral oncogenes and mammalian tumour suppressors drew her into the field of p53. Her group (in parallel with others) discovered the p53 targets PUMA and TIGAR, the latter of which spurred her interest in cancer metabolism.